Aplikasi Kalkulator Full Costing UD Roti Bakery dengan Visual Basic 6.0 - Novia Fatimah; Wigiyanti Wigiyanti (@is The Best : Accounting Information Systems and Information Technology Business Enterprise, 2022)
Consumers are always interested in quality products/services at competitive prices. Competitive prices can be achieved by reducing production costs. To reduce production costs, companies must carefully determine the cost of production. One way to determine it is by using the full costing method, which is the method of calculating the cost of production by calculating all fixed and variable costs. UD Roti Bakery, which is engaged in the production of sweet bread in South Jakarta, calculates the cost of production manually. Errors often occur in this process because the cost elements to be calculated are not small so that the data entry process and the calculation process can be repeated again to ensure the correctness of the calculation results. It is very inefficient. With the aim of streamlining it, the authors built a simple computer-based application using Visual Basic 6.0 programming and the Rapid Application Development method based on UD Roti Bakery's financial report data for the January 2020 period. This research uses quantitative and qualitative methods because the data is in the form of numbers and obtained through interviews and notes direct observation with the company. The final result of this research is a ready-to-use desktop-based computer application called the UD Roti Bakery Full Costing Calculator Application with limitations only for UD Roti Bakery operators and cannot enter more than one date for the same data. This application has implications for giving another color in the computerized calculation of the cost of production using the full costing method.